PROFESSIONAL ADAPTATION OF YOUNG SPECIALISTS: DEFINITION AND LEGAL ASPECT OF IMPLEMENTATION - Kolesnikova V.V. (Pressing Problems of Public Administration, 2018)
The paper highlights approaches to the concept of ’professional adaptation of young specialists’, analyzes the legal aspects of young people’s adaptational capacities, and proves that the system of professional adaptation of staff is used to improve the working process quality. It is stated that professional adaptation of a person allows determining the appropriateness of a person’s choice of profession, creates conditions for adaptation of a young person to professional requirements, rapid acquision of knowledge, skills and abilities, improvement of the level of professional excellence.